Educational Partners’ Perception Towards Inclusive Education - Iryayo, Martin; Anggriyani, Devi; Herawati, Lucky (INKLUSI, 2018)
This study aims at investigating the perceptions of educational partners towards managing and implementing inclusive education, ensuring whether special need students can be wholly admitted and facilitated, and probing on the integration and management of students with physical, moral, and mental problems. The strategy used is centered on a case study with qualitative approach. The researchers applied a semi-structured interview and analyzed the data using content analysis with descriptive-interpretation-pattern coding model. For choosing the participants, quota sampling technique was applied whereby four participants were chosen from every school to represent the sections. The population is made up of all students, teachers, staff, and parents from SMA Yogyakarta, SMA Wates, and SMK Imogiri. Based on the interviews, all the subjects confirmed that inclusive education in the respective schools is critical. Besides, the perceptions of all subjects towards management and implementation of inclusive education does not prove its satisfactory level. [Penelitian bertujuan melihat persepsi orang tua, siswa, guru, dan staf terhadap pengelolaan dan penerapan pendidikan inklusif, memastikan apakah siswa berkebutuhan khusus dapat diterima dan difasilitasi oleh sekolah, dan meyakinkan cara untuk mengintegrasikan dan mengelola siswa dengan masalah fisik, moral, dan mental. Penelitian ini adalah studi kasus dengan pendekatan kualitatif. Peneliti menggunakan wawancara semi-struktural dan menganalisis data dengan analisis konten. Untuk memilih peserta, teknik kuota sampling diterapkan di mana empat peserta dipilih dari setiap sekolah untuk mewakili yang lain. Populasi terdiri dari semua siswa, guru, staf, dan orang tua dari SMA Yogyakarta, SMA Wates, dan SMK Imogiri. Berdasarkan wawancara, semua subjek menegaskan bahwa pendidikan inklusif di sekolah masing-masing masih belum mapan. Selain itu, persepsi semua yang diwawancarai terhadap manajemen dan pelaksanaan pendidikan inklusif tidak benar-benar mengkonfirmasi tingkat pendidikan inklusif yang memuaskan.]